Development of the Gyaku Tsuki and Mawashi Geri Speed Test - Suprianto Kadir; Arief Ibnu Haryanto (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This study aims to develop a speed test for Gyaku Tsuki and Mawashi Geri kicks in Karate. This research is development research with steps that include potential problems, data, product design, design validation, revision design, product testing, product revision, trial use and product revision. The small scale trial was carried out on 10 Karateka who actively participate in the training at the PPLP Gorontalo Province. Meanwhile, a large-scale trial was conducted on 30 Karateka who took part in the training at the PPLP Gorontalo Province. The development research resulted in a valid and reliable form of test, so it was feasible to use it to measure the speed of the Gyaku Tsuki shot and the kick speed of Mawashi Geri.